Development of Accounting Information System at BUMDES to Enchance Financial Performance of the Village - Rachmat; Michael Octavianus; Muh. Yusuf; Muh. Fahmi Basmar; Siti Nur Asia (Institute of Computer Science (IOCS), 2022)
The issue of record management is the most important aspect of preparing financial reports. The application of information technology to the management of village financial reports is crucial to the production of village financial reports that adhere to the ideals of accountability and openness. The financial management process at BUMDes is only visible at the conclusion of a project or the end of the accounting period, i.e. once a year. Consequently, when the director requests periodic or monthly financial statements, the finance department must recap data manually and cannot print financial reports directly. The solution to the aforementioned issues is the design and construction of a financial report information system. This system is supposed to give financial information to the village in a transparent manner and make it easier to manage financial reports. This system manages user data, project data, account data, general journal data, and mandatory reports. The design method utilized in this study is the waterfall method, which takes a methodical and sequential approach to constructing a system. In this system architecture, nine blackbox tests are used to verify that the financial report information system functions have been executed properly and as planned.